GROWTH AND DEVELOPMENT ON INFANTS AGED 0-24 MONTHS WITH A HISTORY OF LOW BIRTH WEIGHT (LBW) IN DR. SOETOMO GENERAL HOSPITAL SURABAYA - Felisita Maritza Abidanovanty; Ahmad Suryawan; Hendy Hendarto (Universitas Airlangga, 2023)
Introduction: Low birth weight (LBW) is the baby's condition with a birth weight of <2500 grams. Babies with LBW tend to have the body not strong as normal babies, so growth or development disorders are often obtained. The condition ensues because the immaturity of some organs will affect the growth and development. Monitoring growth and development through the growth chart and the Denver II. Age 0-24 represents a critical period so that the time is right for the early detection of disorders. Aims: Determine growth according to W/A, H/A, W/H, and HC/A and development according to personal-social, fine motor, language, and gross motor. LBW infants aged 0-24 months Dr. Soetomo General Hospital Surabaya. Methods: Quantitative research using descriptive-analytic study and retrospective approach with a cross-sectional method. The sample was 81 babies who used a total population sampling technique with the medical record. Data processing used univariate and bivariate analysis chi-square. Results: The development dominated by delays measured using 4 domain (personal-social(59.3%), fine motor skills(61.7%), language(66.7%), and gross motor skills(85.2%)). Growth dominated by normal and above based on H/A(60.5%), W/H(55.6%), and H/A(50.6%); except W/A dominated below normal (55.6%). There was no relation between LBW with growth and development based on all domains, except personal-social domains. Conclusion: This study may prove that not all babies with LBW have growth disorder seen from all domains and the development dominate by delay on all domains. There is no relation between LBW with all domains of growth and development except personal-social.